2013
DOI: 10.1039/c3cc44861d
|View full text |Cite
|
Sign up to set email alerts
|

Chiral suprastructures of asymmetric oligothiophene-hybrids induced by a single proline

Abstract: Oligothiophene-proline hybrids were synthesized via click-reaction showing intriguing self-assembly behavior in an aqueous environment by forming chiral superstructures, whose helicity is controlled by the configuration of the amino acid moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 19 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…Baüerle et al 135 explored how the chirality of the biomolecules affected the chiral self-assembly of oligothiophenes. Initially, he decorated the tetrathiophenes with carbohydrates, which resulted in the chirality of the carbohydrate directing the chirality of the assemblies of the carbohydrate−thiophene.…”
Section: Gemini Amphiphiles and Bolaamphiphilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Baüerle et al 135 explored how the chirality of the biomolecules affected the chiral self-assembly of oligothiophenes. Initially, he decorated the tetrathiophenes with carbohydrates, which resulted in the chirality of the carbohydrate directing the chirality of the assemblies of the carbohydrate−thiophene.…”
Section: Gemini Amphiphiles and Bolaamphiphilesmentioning
confidence: 99%
“…The authors further synthesized thiophenes containing a single chiral amino acid (proline) to study the chiral assembly of the conjugates. 135 It was demonstrated that proline with two chiral centers could induce a defined helical packing of the conjugates, whose helicity was controlled by the configuration of the amino acid moiety. Since proline has two chiral centers, the authors also studied how the proline with opposite chirality affects the self-assembly of proline−thiophene.…”
Section: Gemini Amphiphiles and Bolaamphiphilesmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 This observation indicates that the extent of the red-shift in l max (due to unfolding/planarization of the polymer chains upon DNA binding) is related to the charge ratio R À/+ , likely ruling the stoichiometry of the selfassembly. [34][35][36] For dT 20 /CPT, the sign of the ICD is attributed to a preferential right-handed helical conformation of the polymer within the dT/CPT complex. However, above a molar ratio of 1 : 0.6, l max gradually shifts back towards lower wavelengths, eventually yielding a slightly blue-shifted absorption maximum at a 1 : 1 molar ratio, but with a very large shoulder still present in the 500-550 nm region (Fig.…”
Section: Complexation Of Ssdna/cptmentioning
confidence: 99%
“…We have previously shown that a minimalistic (A–B) design based on conjugates of a single proline residue and a quaterthiophene moiety results in chiral, micellar assemblies 19,20. We have also demonstrated that oligoproline scaffolds can guide the hierarchical self-assembly of sterically demanding electron-poor perylene monoimide (PMI) chromophores into a variety of unprecedented nanostructures 2123.…”
Section: Introductionmentioning
confidence: 99%